2015
DOI: 10.3341/kjo.2015.29.4.241
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Manifestations of Acquired Immunodeficiency Syndrome

Abstract: PurposeTo investigate the patterns and risk factors of the ocular manifestations of acquired immunodeficiency syndrome (AIDS) and their correlation with CD4+ count in the era of highly active antiretroviral therapy (HAART).MethodsThis retrospective study examined 127 AIDS patients who presented to Soonchunhyang University Hospital. Data were collected from patient interviews, clinical examinations, and laboratory investigations. Ophthalmologic examinations included the best-corrected visual acuity, intraocular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 46 publications
2
11
1
3
Order By: Relevance
“…A large number of studies have been conducted on the observation of peripheral retinal conditions of fundus diseases through UWF laser scanning ophthalmoscopy [8] , aiming to reduce the burden of ophthalmic outpatient service by combining with optical coherence tomography for virtual retinal outpatient service [9] . With UWF fundus imaging, we confirmed that the most common HIV-related fundus changes were HIV-related MVR, followed by CMVR, which met the results of another group's study [3,10] . Other changes included HIV related/non-related lesions: optic disc edema, peripheral lattice degeneration, subretinal lesions, and PORN, etc.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A large number of studies have been conducted on the observation of peripheral retinal conditions of fundus diseases through UWF laser scanning ophthalmoscopy [8] , aiming to reduce the burden of ophthalmic outpatient service by combining with optical coherence tomography for virtual retinal outpatient service [9] . With UWF fundus imaging, we confirmed that the most common HIV-related fundus changes were HIV-related MVR, followed by CMVR, which met the results of another group's study [3,10] . Other changes included HIV related/non-related lesions: optic disc edema, peripheral lattice degeneration, subretinal lesions, and PORN, etc.…”
Section: Discussionsupporting
confidence: 85%
“…Once an infectious retinitis appeared in AIDS patients, lesions would rapidly progress, causing irreversible vision loss or blindness. Nearly 19.7% to 44.25% of HIV/AIDS patients had fundus damages [2][3] . In the Post-HAART-Era, the most common fundus opportunistic infection is still cytomegalovirus retinitis (CMVR), which is also known as the main cause of vision loss in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Cited by many authors,7,8,10 a direct relationship of IOP with TCD4 in this study was not found, probably because the groups of patients with the virus under treatment were very homogeneous (well controlled of their disease) and the N of patients with the virus without treatment was small.…”
Section: Discussioncontrasting
confidence: 58%
“…Similar to diabetes, HIV infection can cause various OMs, which have become a global health problem in patients with chronic diseases. Although the OMs prevalence has decreased compared to the pre-HAART era, as many as 48% of HIV-infected patients have been diagnosed with OMs in the HAART era [ 6 , 11 , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] ]. Early diagnosis of OMs is critical for the timely treatment and determination of the prognosis of HIV infection, as the impaired visual function can decrease productivity [ 9 , 17 , 18 , 23 , 24 ], and increase the cost of treatment [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%